The "locking and dragging" technique a facilitated crossover balloon occlusion technique for complex iliofemoral anatomy in transcatheter aortic valve replacement. Issue 6 (14th August 2021) - Briguori, Carlo; Scarpelli, Mario
Abstract: Crossover balloon occlusion technique (CBOT) has been proposed to ensure adequate closure of the arterial access used for transcatheter aortic valve replacement (TAVR). However, the CBOT performed through the contralateral femoral artery could be challenging in cases of excessively tortuous and calcified vessels or in the presence of narrow iliac carina angles. We describe a novel technique to facilitate the advancement the peripheral balloon through the contralateral femoral artery up to the target iliofemoral system in order to facilitate access site hemostasis. The present "locking and drugging" technique takes advantages from two mechanical aspects: (a) the locking of the 0.018″ wire between the vessel wall and the TAVR delivery system or the dedicated sheath, which facilitate the crossover of the balloon in the contralateral iliofemoral system, preventing its prolapse into the aorta at the carina level and (b) the dragging of the balloon advanced into the contralateral iliofemoral system during the retrieve of the TAVR delivery system or the dedicated sheath.